A cascade of complications after liver transplantation: A case report. (2020) - Shadhu, Kamleshsingh; Ramlagun, Dadhija; Qin, Jianjie; Xia, Yongxiang
Abstract: Introduction: Postoperative complications after liver transplantation are a clinical challenge for surgeons and their awareness and management needs to be reported. Case presentation: A 50-year-old male patient came to our hospital 40 days after liver transplantation. The patient was on Tacrolimus. He had anastomotic biliary stricture, nephrotoxicity, huge haematoma transformation and paralysis of left lower limb. He underwent percutaneous transhepatic cholangiography drainage (PTCD), artificial arterio-venous fistula formation, dialysis, and blood transfusion. Conclusion: We conclude that important cooperation is needed between patient and surgical team to solve the cascade of complications due to side effects of postoperative drugs. Highlights: Tacrolimus (FK506) cause side effects like nephrotoxicity. Tacrolimus (FK506) level was 22 ng/mL. Continual renal replacement therapy (CRRT). Large haematoma formation and extensive haemorrhage at the left lumbar muscle, extending into the left lower leg. Discharged 31 days later, and close follow-up is done.